Status of the frog genus sphoenohyla with a synopsis of the species (1957)
There is, in South America, a small group of hylid frogs usually referred to as the aurantiaca group. The frogs of this group are known by their bright green or greenish yellow color in life, and their pointed and projecting snouts. In preservative they tend to assume a bent and cramped position and to fade rapidly, first to an orangish hue and then to a creamy white.